First report of Planktothrix rubescens bloom from the Algerian freshwater reservoir Hammam Debagh - Fatma Zohra GUELLATI; Hassen TOUATI; Skander KADRI; Amel SAOUDI; Luc BRIENT; Mourad BENSOUILAH (Studia Universitatis Babeș-Bolyai. Biologia, 2024)
Massive cyanobacteria blooms have become a worldwide concern problem due to the multiple nuisances they can cause. The impacts of climate change are distinct from other environmental constraints controlling its population dynamics. The current study was accomplished in the monomictic reservoir Hammam Debagh (North-Eastern Algeria). A sampling campaign was conducted during May and June 2012 in four surface sampling stations and the water column in the center of this reservoir. This study aims to investigate the surface bloom of Planktothrix rubescens (De Candolle ex Gomont 1892) Anagnostidis and Komarek, 1988; observed for the first time in an Algerian reservoir with a focus on the environmental variable changes in 2012. During this thick epilimnetic bloom, P. rubescens spread in all water column layers, reaching 6.4 x 106 cells mL-1 at 2m from the surface recorded on 11.05.2012. Meanwhile, at the surface P. rubescens abundances ranged from 3 x 105 to 3.6 x 106 cells mL-1. The biomass was so high that the signal from the phycocyanin probe became saturated attending a value of 200 μg L-1 PC in the top 1 m. In addition, the biogenic compounds especially P-PO4 and NO3 show a high concentration of 0.48 mg L-1 and 5 mg L-1 respectively. The red pigmented cyanobacterium bloom altered environmental conditions in the reservoir Hammam Debagh, since primarily oxygen concentration shows a minimum of 2.63 mg L-1 and water transparency did not exceed 1m (min= 40cm). The vertical profile of temperature performed on 29.05.2012 over 33m; shows a stratified water column ranging from 22.6°C in the upper subsurface to 9.8°C in the bottom hypolimnion. Finally, suitable meteorological conditions were observed during 2012.